2021
DOI: 10.1021/acssuschemeng.1c05604
|View full text |Cite
|
Sign up to set email alerts
|

Trans-2-Butene-1,4-Diol as an Olefinic Building Block to Prepare Biobased Unsaturated Copolyesters with High Molecular Weight: Synthesis, Characterization, and Physical Properties

Abstract: A series of biobased poly(butylene succinate-co-trans-butene succinate) (PBStBS) was prepared by copolymerizing biobased trans-2butene-1,4-diol(tB), succinic acid, and 1,4-butanediol via a two-step polycondensation. NMR and gel permeation chromatography characteristics indicated that the isomerization and branching side reactions were prevented in PBStBS synthesis. Random copolyesters with high number average molecular weights (M n ) over 40 kDa were achieved. Despite being random, these PBStBS can crystallize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Thus, we tried to use theoretical models (ES12-ES17) for the random copolymers for the calculation of the crystal compatibility of HP and HV. 52,53 As shown in Fig. 9(C), the experimental T 0 m values highly match with the insertion-rejection theory (Wendling-Suter model).…”
Section: Polymer Chemistry Papersupporting
confidence: 74%
“…Thus, we tried to use theoretical models (ES12-ES17) for the random copolymers for the calculation of the crystal compatibility of HP and HV. 52,53 As shown in Fig. 9(C), the experimental T 0 m values highly match with the insertion-rejection theory (Wendling-Suter model).…”
Section: Polymer Chemistry Papersupporting
confidence: 74%
“…Thus, it is further demonstrated that no branching reaction occurred during polymerization. In addition, only the proton of cis double bond is detected, indicating no isomerization of the double bonds taking place during polycondensation. , Hence, 1 H NMR and GPC results confirm the successful synthesis of the desired linear unsaturated polyesters without the branching or the isomerization of double bonds.…”
Section: Resultsmentioning
confidence: 59%
“…In addition, only the proton of cis double bond is detected, indicating no isomerization of the double bonds taking place during polycondensation. 50,53 Hence, 1 H NMR and GPC results confirm the successful synthesis of the desired Cooling and Heating Thermograms. The nonisothermal crystallization and subsequent melting process of the prepared unsaturated polyesters were investigated via DSC, as shown in Figure 2.…”
Section: ■ Experimental Sectionmentioning
confidence: 53%
“…Although several attempts (like high-temperature crystallization, solution crystallization, and stretch-induced crystallization) have been made, no crystallization phenomenon of it could be observed. This stereo-isomer effect on the crystallization behavior is attributed to the main difference between 3,4-TFDCA and 2,5-TFDCA being the lower symmetry of the former, and the difference in polyester’s δ value also influences the crystallization ability to some degree. Additionally, these polyesters both exhibited a one-step thermal decomposition process under a N 2 atmosphere (Figure d). The related results of TGA experiments indicated that the position (2,5/3,4) of the carboxylic acid groups hardly affected the thermal stability of TFDCA-based polyesters.…”
Section: Resultsmentioning
confidence: 99%